Refleksi Kepala Madrasah dalam Kebijakan Pendidikan di Madrasah Nidaaul Ummah Al-Islamiyah Ciracas Jakarta Timur - Habib Zakaria Bahasyim; Waisul Qurni; Alwi; Muhammad Ubaidillah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2026)
The madrasah principal holds a strategic role in determining the direction and quality of education through a series of reflectively formulated, implemented, and evaluated policies. The urgency of this study is grounded in the reality that reflective madrasah principal leadership is a key factor in transforming the quality of Islamic education in Indonesia, particularly within faith-based educational institutions facing the challenges of modernity. This study aims to examine in depth the madrasah principal's reflection in the policy formulation and implementation process at Madrasah Nidaaul Ummah Al-Islamiyah Ciracas East Jakarta, as well as to analyze the impact of these policies on madrasah educational progress. The method employed is a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation studies. Research subjects included the madrasah principal, teachers, educational staff, and parents. Data analysis was conducted through stages of data reduction, data presentation, and conclusion drawing based on the Miles and Huberman model. The results indicate that the principal of Madrasah Nidaaul Ummah Al-Islamiyah Ciracas East Jakarta has carried out a reflective role in educational policy formulation encompassing academic dimensions, Islamic character, and human resource development. Policy implementation was carried out collaboratively involving all madrasah stakeholders. The impacts include improved learning quality, strengthened religious culture, enhanced teacher professionalism, and positive responses from the community and parents.